Safety asssessment of iopromide contrast media: a narrative review focusing on adverse events - Joaquim João José; Matos Cristiano; Mateos-Campos Ramona (Current Issues in Pharmacy and Medical Sciences, 2023)
Many clinical contexts require radiological exams based on contrast media administration. Iodinated contrast media (ICM) represents one of the most studied contrast agents often used in radiological examinations. ICM vary widely in their physicochemical properties, clinical uses, as well as in the incidence of adverse reactions (ARs). Therefore, a basic understanding of ARs occurrence, risk factors, clinical features, and management of ICM is increasingly important in clinical practice. Iopromide is a nonionic ICM widely used in clinical practice due to its favourable safety profile and numerous applications. This narrative review provides a comprehensive report of the available data concerning iopromide ARs. It also analyses iopromide ARs occurrence and frequency with diverse potential risk factors such as age, sex and pre-existing conditions.